Birds: verifying documentation of an extraordinary sight record submitted by Thomas H. Kent, April 30 1981 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
A form documenting the sighting of a Peregrine Falcon at Muskrat Slough submitted by Thomas Kent. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1981. Epson - sheet feed